ANALISIS PERBAIKAN DEFECT PADA PRODUK BATA RINGAN DENGAN MENGGUNAKAN METODE RCA (ROOT CAUSE ANALYSIS) PADA SALAH SATU PERUSAHAAN BATA RINGAN DI SERANG TIMUR - Purwanto Bayu Sugiharto; Endi Furqon; Ogie Kustiadi (LPPM Universitas Bina Bangsa, 2023)
Power Block Indonesia is a company engaged in the production of light bricks. Based on the document on the production of light brick raw materials, it was found to resist fractures, imprecision, non-standard wet and debris. This condition can hamper the quality of production in the manufacture of lightweight bricks due to many rejections in the production process. Product reject and result in low quality in the production of light brick making with a reject proportion of 4% that has been determined by the company. The purpose of research is to improve product quality, and reduce product. The research method used is the RCA (ROOT CAUSE ANALYSIS) method, which is the method used to improve product quality at PT. Power Block Indonesia. Observations and interviews conducted in the light brick production area, there are several schools that must be taken immediately, including conducting regular training. Corrective action part of the quality caused by changes in quality from a predetermined standard. From the results of data analysis and discussion that the production process is out of control or is still experiencing irregularities. Based on the Pareto diagram it can damage the type of damage that occurred in PT. Power Block Indonesia is 88%, not precise is 0.07%, non-standard is 2.65%, wet is 0.39%, and debris is 9.14%. December 2021